(untitled) (CIPEEX, 2025)
Hemoglobin is a fundamental protein for life, responsible for carrying oxygen from the lungs to the tissues. The World Health Organization (WHO) defines anemia as the condition in which hemoglobin levels are below normal, often caused by a lack of nutrients such as iron, zinc, vitamin B12, and proteins. When hemoglobin decreases, the body attempts to adapt by redirecting blood to vital organs and increasing cardiac output. However, these mechanisms are not always sufficient, especially in more vulnerable individuals. The most common symptoms of iron-deficiency anemia are apathy, fatigue, weakness, and pallor of the skin and mucous membranes, which may worsen over time and further compromise energy and well-being. In general, anemias can be classified according to the duration (acute or chronic), the main cause (reduced red blood cell production, increased destruction, or blood loss), and also by hematimetric indices from the complete blood count (normocytic/normochromic, macrocytic, or microcytic/hypochromic). These parameters help health professionals investigate, diagnose, and monitor the patient’s clinical progress. The analysis of hematological indicators obtained from blood tests aims to identify, differentiate, and monitor the progression of different types of anemia and other hematological diseases. This summary encompasses selected studies analyzed to understand the diagnosis, classification, and monitoring of anemias. It is a literature review based on data collected from databases such as Google Scholar, covering publications from the last five years. The review indicates that the laboratory diagnosis of anemia begins with the interpretation of parameters provided by the complete blood count, especially those related to the red blood cell series (erythrogram). Among the main indices evaluated are hemoglobin concentration (Hb), the percentage of red blood cells relative to total blood volume (hematocrit or Ht), the total red blood cell count (RBC), and reticulocyte count. Erythrocyte analysis through the complete blood count provides essential information on hematimetric indices, allowing assessment of the patient’s hematological status. These parameters also include the mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), and red cell distribution width (RDW), as well as morphological evaluation of red blood cells. From this perspective, the complete blood count is the main blood analysis tool, essential for the differentiation, diagnosis, and monitoring of anemic conditions. It allows tracking the progress of treatment, whether pharmacological or not, and is also crucial for early diagnosis and monitoring of diseases such as infections and leukemias, as well as for routine evaluations, preoperative assessments, and monitoring of various health treatments.